Characteristics of Pregnant Women who Experience Chronic Energy Deficiency in the Community Health Center - Nuryana, Riska; Sumarmi; Mantasia; Agustina (Omni Nursing Journal, 2025)
Background:  Malnutrition, iron deficiency anemia, and macro- and micronutrient deficiencies, including chronic energy deficiency (CED/SEZ), are common nutritional problems among pregnant women. Objective: To determine the characteristics of pregnant women experiencing Chronic Energy Deficiency (CED/SEZ) in the Puskesmas working area. Methods: This study employed a quantitative, descriptive, cross-sectional design. Results: The majority of pregnant women with CED/SEZ were aged <20 years (25 respondents; 52.1%). Most belonged to the primary parity category (26 respondents; 54.2%), and 33 respondents (68.8%) were unemployed. In terms of education, 24 respondents (50.0%) had only basic education (elementary or junior high school). Conclusion: Pregnant women aged <20 years or >35 years require greater nutritional support. The nutritional status of pregnant women may be influenced by parity, birth outcomes, and the number of children. Mothers who have given birth to four or more children are at greater risk of experiencing CED/SEZ.